Evidence that Maackia amurensis seed lectin (MASL) exerts pleiotropic actions on oral squamous cells with potential to inhibit SARS-CoV-2 infection and COVID-19 disease progression - Sheehan, Stephanie A. (Exp Cell Res, 2021)
COVID-19 was declared an international public health emergency in January, and a pandemic in March of 2020. There are over 125 million confirmed COVID-19 cases that have caused over 2.7 million deaths worldwide as of March 2021. COVID-19 is caused by the SARS-CoV-2 virus. SARS-CoV-2 presents a surface “spike” protein that binds to the ACE2 receptor to infect host cells. In addition to the respiratory tract, SARS-Cov-2 can also infect cells of the oral mucosa, which also express the ACE2 receptor. The spike and ACE2 proteins are highly glycosylated with sialic acid modifications that direct viral-host interactions and infection. Maackia amurensis seed lectin (MASL) has a strong affinity for sialic acid modified proteins and can be used as an antiviral agent. Here, we report that MASL targets the ACE2 receptor, decreases ACE2 expression and glycosylation, suppresses binding of the SARS-CoV-2 spike protein, and decreases expression of inflammatory mediators by oral epithelial cells that cause ARDS in COVID-19 patients. In addition, we report that MASL also inhibits SARS-CoV-2 infection of kidney epithelial cells in culture. This work identifies MASL as an agent with potential to inhibit SARS-CoV-2 infection and COVID-19 related inflammatory syndromes.